Maternal and Fetal-Placental Effects of Etanercept Treatment During Rats’ Pregnancy - Araujo, Gabriel Gomes; dos Passos Junior, Rinaldo Rodrigues; Lunardi, Rosaline Rocha; Volpato, Gustavo Tadeu; Soares, Thaigra Sousa; Giachini, Fernanda Regina; Lima, Victor Vitorino (Frontiers in Physiology, 2022)
Etanercept is a tumor necrosis factor alpha (TNF-α) inhibitor chronically used to treat autoimmune diseases. However, the use of etanercept during pregnancy still needs to be further investigated. The aim of this study is to evaluate the etanercept treatment during pregnancy, analyzing maternal reproductive performance, fetal outcomes and placental repercussions. Wistar rats (200-250 g) were mated and randomly distributed into 2 experimental groups: control and etanercept (n=10 animals/group). Treatments with etanercept (0.8 mg/kg, s.c.), or saline (control group) were carried out on days 0, 6, 12 and 18 of gestation. On the morning of the 21st day of pregnancy, rats were euthanized in a CO2 chamber and submitted to laparotomy to remove the fetuses, placentas, ovaries, and maternal organs. There were no differences between groups in the following parameters: water and food consumption; placental efficiency; reproductive parameters, including number of corpora lutea and implants, reabsorption, and pre- and post-implantation losses. However, etanercept treatment increased liver weight, reduced fetal and placental weight, decreased the placental junction zone, reduced the percentage of normal fetuses, and increased visceral or skeletal fetal abnormalities. Therefore, etanercept resulted in damages more related to fetus and placenta. However, more studies with different doses are required to better predict possible injuries elicited using etanercept during pregnancy.